Bioinsecticidal activity of Philodendron bipinnatifidum (Research, Society and Development, 2020)
Brazil is one of the few countries in the world with a well-structured program to monitor the resistance of Aedes aegypti, especially to organophosphates. In this context, new alternatives have been proposed, such as the use of bioinsecticides, such as the species Philodendron bipinnatifidum, native to the Atlantic Forest. Objective: The objective of the present study was to evaluate the larvicidal activity of the crude extracts of the stem, fruit, leaf and petiole of P. bipinnatifidum on the larvae of the third stage of A. aegypti. Methodology: The crude extracts were obtained from the stem, fruit, leaf and petiole of P. bipinnatifidum from specimens located in the municipality of Prudentópolis-PR. The technique of obtaining the extracts was by dynamic maceration with renewal of the solvent (alcohol 96ºGL). Larvicidal activity was performed by the larval immersion technique, using larvae of the third stage of A. aegypti, in concentrations ranging from 200.0 to 0.4 mg/mL. Results: The extracts of the stem, fruit, leaf and petiole showed larvicidal activity on A. aegypti with LC50 (50% lethal concentration) of 78.9 mg/mL, 46.6 mg/mL, 65.8 mg/mL and 51.8 mg/mL, respectively, showing that the crude extracts of the fruit and petiole showed greater larvicidal potential. Conclusion: These results stimulate the isolation of biomolecules present in the extract, aiming at the development of products for the control of this culicid.